G Quadruplex in Plants: A Ubiquitous Regulatory Element and Its Biological Relevance - Yadav, Vikas; Hemansi,; Kim, Nayun; Tuteja, Narendra; Yadav, Puja (Frontiers in Plant Science, 2017)
G quadruplexes (G4) are higher-order DNA and RNA secondary structures formed by G-rich sequences that are built around tetrads of hydrogen-bonded guanine bases. Potential G4 quadruplex sequences have been identified in G-rich eukaryotic non-telomeric and telomeric genomic regions. Upon function, G4 formation is known to involve in chromatin remodeling, gene regulation and has been associated with genomic instability, genetic diseases and cancer progression. The natural role and biological validation of G4 structures is starting to be explored, and is of particular interest for the therapeutic interventions for human diseases. However, the existence and physiological role of G4 DNA and G4 RNA in plants species have not been much investigated yet and therefore, is of great interest for the development of improved crop varieties for sustainable agriculture. In this context, several recent studies suggests that these highly diverse G4 structures in plants can be employed to regulate expression of genes involved in several pathophysiological conditions including stress response to biotic and abiotic stresses as well as DNA damage. In the current review, we summarize the recent findings regarding the emerging functional significance of G4 structures in plants and discuss their potential value in the development of improved crop varieties.